Analysis of the Environmental, Social, and Governance (ESG), Retention Ratio, and Leverage Impacts on Stock Returns with Company Value as a Moderation Variable - Pratama, Dimas Umbara; Robinson, Robinson (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2024)
Efforts to enhance company performance through adherence to corporate governance principles are demonstrated in the company's comprehensive ESG (Environmental, Social, and Governance) disclosures. In evaluating these disclosures, it is imperative to weigh the impact of leverage and retention ratio. The survey conducted by Globescan and the Global Reporting Initiative (GRI) has revealed a significant lack of awareness regarding the importance of these factors among typical companies in Indonesia. Hence, this study examined the ESG, retention ratio, and leverage impacts on stock returns with company value as a moderation variable. The samples of this study comprised 14 financial companies listed on the Indonesia Stock Exchange within the timeframe of 2018-2022. Data for the analysis were extracted from the IDX website and the official websites of the respective companies. Employing Eviews 9 software, multiple linear regression analysis was conducted to unravel insights into the relationships under scrutiny. The discerned outcomes unveiled that neither ESG nor leverage significantly impacted stock returns. In contrast, the retention ratio emerged as a potent factor with a noteworthy influence. The company value could moderate the ESG and the retention ratio impacts on stock returns, yet it proved ineffective in moderating the leverage impact on stock returns.